Determination of thermodynamic properties of aluminum based binary and ternary alloys - Altintas, Yemliha; Aksoz, Sezen; Keslioglu, Kazim; Marasli, Necmettin (ELSEVIER SCIENCE SA, 2015)
In the present work, the Gibbs-Thomson coefficient, solid-liquid and solid-solid interfacial energies and grain boundary energy of a solid Al solution in the Al-Cu-Si eutectic system were determined from the observed grain boundary groove shapes by measuring the thermal conductivity of the solid and liquid phases and temperature gradient. Some thermodynamic properties such as the enthalpy of fusion, entropy of fusion, the change of specific heat from liquid to solid and the electrical conductivity of solid phases at their melting temperature were also evaluated by using the measured values of relevant data for Al-Cu, Al-Si, Al-Mg, Al-Ni, Al-Ti, Al-Cu-Ag, Al-Cu-Si binary and ternary alloys. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aluminum alloy; Thermodynamic properties; Interfacial energy; Solidification; Crystal growth; LIQUID INTERFACIAL ENERGY; AL-CU; SI ALLOYS; ELECTRICAL-RESISTIVITY; SURFACE ENERGIES; SYSTEM; EQUILIBRIUM; PHASE; NEOPENTYLGLYCOL; MICROSTRUCTURE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering